Evidence of warm and humid interstadials in central Europe during early MIS 3 revealed by a multi-proxy speleothem record - Weber, Michael; Schröder-Ritzrau, Andrea (Quaternary science reviews, 2018)
Marine Isotope Stage 3 (MIS 3, 57-27 ka) was characterised by numerous rapid climate oscillations (i.e., Dansgaard-Oeschger (D/O-) events), which are reflected in various climate archives. So far, MIS 3 speleothem records from central Europe have mainly been restricted to caves located beneath temperate Alpine glaciers or close to the Atlantic Ocean. Thus, MIS 3 seemed to be too cold and dry to enable speleothem growth north of the Alps in central Europe. Here we present a new speleothem record from Bunker Cave, Germany, which shows two distinct growth phases from 52.0 (+0.8, −0.5) to 50.9 (+0.6, −1.3) ka and 47.3 (+1.0, −0.6) to 42.8 (±0.9) ka, rejecting this hypothesis. These two growth phases potentially correspond to the two warmest and most humid phases in central Europe during MIS 3, which is confirmed by pollen data from the nearby Eifel. The hiatus separating the two phases is associated with Heinrich stadial 5 (HS 5), although the growth stop precedes the onset of HS 5. The first growth phase is characterised by a fast growth rate, and Mg concentrations and Sr isotope data suggest high infiltration and the presence of soil cover above the cave. The second growth phase was characterised by drier, but still favourable conditions for speleothem growth. During this phase, the δ13C values show a significant decrease associated with D/O-event 12. The timing of this shift is in agreement with other MIS 3 speleothem data from Europe and Greenland ice core data.
Gesehen am 28.06.2019